Phenological studies of flowering and fruiting of peanut butter fruit (Bunchosia armeniaca (Cav.) DC.) - Nithya; Manjusha A.V., Meera (Journal of Tropical Agriculture, 2024)
The study was carried out at Regional Agriculture Research Station, Pilicode and College of Agriculture Padannakkad from January 2022 to December 2022. The objectives were to study phenological stages regarding flowering, fruit setting and fruit development in peanut butter fruit. The flower bud initiation was started by the end of March. From flower bud initiation to anthesis it took about 28 days. The period of flowering and fruiting was observed from April to September, flowering peaks in three months viz., April, May and June. Whereas fruiting peaks in the months of May, June and July. Yellow-coloured flowers are borne on racemose inflorescence. From fruit set to fruit ripening, it took about 50 days. Fruits are found in clusters. Green-coloured fruits produced during the fruit set gradually change their colour to greenish yellow then orange and red at maturity.